Understanding of medical students regarding the clinical scope of the plastic surgery specialty - Pedro Freire Guerra Boldrin; Júlia Alves Nascimento Rodrigues; Laíne Ribeiro Antonelli; Maria Luísa Peres Vilela; Giovana Alcino Carneiro; Paulo Paula Piccolo (Revista Brasileira de Cirurgia Plástica)
Introduction: Plastic surgery is popularly known for its performance in body aesthetics. Besides, it includes burns, microsurgery, hand and craniomaxillofacial surgery. Due to the diversity of medical specialties, many of the procedures in which plastic surgeons are trained are also performed by other specialists, which may justify the population's lack of knowledge regarding the rich plastic work. The objective is to understand the Brazilian medical students' comprehension of the plastic surgery clinical scope. Methods: Cross-sectional study, applying an online questionnaire with Google Docs platform using the inclusion criteria of being a medical student and over eighteen years old. It consisted of twelve clinical cases sent to participants through social networks. At the end of 99 days after the link's release, the questionnaire was closed, and the answers were counted with Windows Excel. Results: Sample composed of 423 participants, with a female majority and an average age of 22.23 years, with a higher prevalence of the third year of the academic clinical cycle. It was noticed that students are familiar with plastic surgeons' actions in the aesthetic field, breast reconstruction after carcinoma, and reparative treatment of burns. Academics poorly indicated the treatment of fractures in the craniomaxillofacial complex and the palmar tendons' laceration approach. Conclusion: Students have a good understanding of the role of plastic surgeons in the aesthetic field.